Raman spectra of water in fluid inclusions: II. Effect of negative pressure on salinity measurement. (17th March 2015) - Tarantola, Alexandre; Caumon, Marie‐Camille; Marshall, Craig P.
<x xml:space="preserve">Abstract</x> Salinity of fluid inclusions is usually determined by microthermometry, but it becomes unsuitable in case of metastability of the aqueous fluid because of thermodynamics indetermination. Raman microspectrometry of water in individual aqueous fluid inclusions can provide chemical information about fluid composition, in particular the concentration of chloride ions. The regular method consists in correlating the deformation of the OH stretching vibration band of liquid water in the region assigned to hydrogen‐bonded OH groups, with chloride concentration. In order to evaluate the ability of Raman spectroscopy to determine salinity of metastable fluid inclusions, the Raman spectra of water trapped in two natural fluid inclusions were recorded at various temperatures in two physical states of the liquid phase, at equilibrium with vapor or metastable at negative pressure. The difference in salinity measured in the two states increased when temperature decreased, i.e. when the intensity of metastability increased. Metastability was then expressed in negative pressure scale (MPa) by thermodynamic modeling of the fluid trapped in the inclusions and correlated to salinity relative difference. The quantification of this effect led us to conclude that salinity expressed in mass% NaCleq. was overestimated of about 1% per 10–15 MPa of negative pressure. If the negative pressure can be quantified, it is thus possible to determine the salinity of metastable fluid inclusions by Raman spectroscopy. Copyright © 2015 John Wiley & Sons, Ltd.